2020
DOI: 10.1111/faam.12276
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted not‐for‐profit accountability: Its measurement, cultural context, and impact on perceived social performance

Abstract: This study investigates the multifaceted nature of accountability mechanisms in Australian not‐for‐profit organizations (NFPs), the association between organizational culture and the use of these mechanisms, and the association between accountability mechanisms and perceived NFP social performance. The findings support the theorization of multifaceted accountability mechanisms in NFPs, including upward accountability (to funders), downward accountability (to clients), and lateral accountability (to employees).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…The search for greater accountability, the need for valuable and context-oriented HC information (not merely quantitative), and the establishment of proper and specific non-financial reporting models constitute some key issues for the whole social economy sector [25,26]. Previous research as that by Tejedo-Romero and Araujo (2021) showed that companies are adapting to new regulations and voluntarily disclosing information on human capital, a trend that signals their commitment to responsible attitudes towards employees and stakeholders [27].…”
Section: Methodsmentioning
confidence: 99%
“…The search for greater accountability, the need for valuable and context-oriented HC information (not merely quantitative), and the establishment of proper and specific non-financial reporting models constitute some key issues for the whole social economy sector [25,26]. Previous research as that by Tejedo-Romero and Araujo (2021) showed that companies are adapting to new regulations and voluntarily disclosing information on human capital, a trend that signals their commitment to responsible attitudes towards employees and stakeholders [27].…”
Section: Methodsmentioning
confidence: 99%
“…Two features of human service NFPs that define those organizations are (i) they have multiple stakeholders (Hall & O'Dwyer, 2017; Jiao, 2021) and (ii) the maintenance of high‐quality service provision is dependent on communication, cooperation, and collaboration across employees with different disciplinary functions and skills (Kastberg & Siverbo, 2013; Valero et al., 2015). With respect to the first feature, Tucker and Parker (2015, p. 120) assert that
the NFP organisations’ arena is highly institutionalised in a number of respects.
…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…In the NFP accountability literature, most emphasis has been placed on the importance of discharging accountability to stakeholders through various “means,” known as accountability mechanisms, including performance evaluation, reports, client participation, and social accounting, with most of the mechanisms being reporting based (Ebrahim, 2010; Jiao, 2021; Yates et al., 2021). These mechanisms are subject to criticism that they do not form a coherent “system,” they are largely post hoc in nature and are typically driven and shaped by the demands of external stakeholders (Agyemang et al., 2019; Yates et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These two principles work in very different ways, and only a very skilled social entrepreneur can make the company viable on both objectives (Bruneel et al, 2016). More than in the past, SEs must now pay attention to economic performance, due to the growing pressure exerted by various stakeholders, which could eventually compromise the achievement of social goals (Esposito, Brescia, et al, 2021; Jiao, 2020; Schubert & Willems, 2021; Wellens & Jegers, 2014). For this reason, we analyze sustainable SEs (Esposito & Antonucci, 2021) and if they simultaneously pursue economic, social, and environmental goals (Esposito, Braga, et al, 2021; Kamaludin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%